Hubungan Dukungan Keluarga dengan Kepatuhan Minum Obat Pada Penderita Hipertensi : Literature Review - Margiati, Raphelia; Panma, Yuanita (Maternal & Neonatal Health Journal, 2026)
Hypertension is a condition in which a person experiences an increase in blood pressure beyond normal limits. This disease is one of the non-communicable diseases that needs to be watched out for. Adherence to taking medication in hypertensive patients is very important because it can control blood pressure to remain stable, so that damage to organs can be reduced. Hypertensive patients need care throughout their lives, therefore hypertensive patients really need family support to get information about hypertension problems. To determine the relationship between family support and adherence to taking medication in patients with hypertension. The search strategy was carried out through Google Scholar. The research method used was literature review with a total of seven articles. Showed that there was a significant relationship between family support and adherence to taking medication in patients with hypertension. This literature review is to find out the relationship between family support and adherence to taking medication in patients with hypertension. It is hoped that people with hypertension can improve adherence to taking medication so as to prevent or reduce an increase in blood pressure or complications